Preparation and characterization of poly (L-leucine)-1,3-diamino propane (PLL)-lithium iodide (Lil) as solid polymer electrolyte / Norazmawati Lahazan - Lahazan, Norazmawati (2009)
The quest of new materials for solid electrolyte is unlimited. In this work, poly amino acid that is poly (L-Leucine)1,3-diamino propane (PLL) has been chosen as the host for solid polymer electrolyte. Solid polymer electrolyte containing PLL was prepared via low temperature sintering method. The PLL was mixed with lithium iodide (LiI) at various wt %, ground, pelletized and then sintered at 90°C in a vacuum oven to initiate the reaction and maintained at that temperature for 3 days (72 hours). The electrical conductivity of the samples was measured using impedance spectroscopy technique. The maximum conductivity of 1.7 X 10-4 S/cm at room temperature was obtained for the sample containing 50 wt % of LiI. The conductivity was contributed by lithium ions since the ion transfer move with high mobility in the system. The ionic transference number of the lithium ions for the sample with the highest electrical conductivity is 0.88. The ionic conductivity was related to the structure of the material and was investigated using infrared technique (FTIR). FTIR was employed to verify the chelation of cation at C=O of PLL at wavenumber of 1642 cm-1. The band at 1642 cm-1 have shifted to lower wavenumber and this confirms that complexation has occurred in the sample. The X-ray diffraction result revealed that the poly(L-Leucine)1,3-diamino propane (PLL) is semi-crystalline and Lil is crystalline in nature. The XRD diffractogram of various PLL-LiI samples showed that some of the peaks have disappeared and the peak at 28 = 10 - 18° has broadened in PLL-LiI samples. The sample has become more amorphous with Lil added. The temperature dependence conductivity was done from 30°C to 90°C to determine the conduction mechanism. It was found that the conduction mechanism follows the Vogel-Tamman-Fulcher (VTF) characteristics.